Five-year evaluation of the antimicrobial susceptibility patterns of bacteria causing bloodstream infections in Iran - Babak Pourakbari; Alireza Sadr; Mohammad Taghi Haghi Ashtiani; Setareh Mamishi; Mahdi Dehghani; Shima Mahmoudi; Ali Salavati; Farhad Asgari (Journal of Infection in Developing Countries)
Introduction: Bloodstream infections (BSI) are a serious cause of morbidity and mortality worldwide. Emerging antimicrobial drug resistance among bacterial pathogens causing BSI can limit therapeutic options and complicate patient management.